Pengolahan Limbah Kotoran Sapi Menjadi Pupuk Organik di Desa Kuwurejo Kecamatan Bluluk, Kabupaten Lamongan - Iqbal Rizqiawa, Mohammad; Wahid, Abdur Rohman; Khanifa; chelsia, putri nabila (ISAS (Indonesian Society of Applied Science), 2023)
This community service activity was carried out in the Bluluk sub-district, precisely in the Kuwurejo village, Bluluk sub-district. This activity aims to provide an understanding to the Kuwurejo village community about the utilization of cow dung waste by processing it into Bokashi organic fertilizer. The method used in this activity uses a material presentation approach and direct practice of making organic fertilizer from cow dung. The results of the training on making bokashi or organic fertilizers that have been carried out can be concluded that the activities went smoothly according to plan. In addition, the enthusiasm of the community is quite high, it can be seen during the training activities for making organic fertilizers, almost 70% of the participants filled the training venue.